Testing the quality of a carrier: a field experiment on lizard signalers. - Olsson, M; Healey, M; Wapstra, E; Uller, T (2009)
In the Australian painted dragon lizard (Ctenophorus pictus), males occur in two different morphs with respect to gular color, with or without a yellow bib. Males without a bib lost within-clutch paternity significantly more often to rivals than bibbed males. Thus, it appears that bibs identify some phenotypic advantage linked to competitive ability. To test whether this could be related to whole-organism capacity to withstand an increased workload (due to better health and vigor, or evolved differences in self-maintenance), we implanted males with a lead pellet (loaded), Styrofoam pellet (controls), or sham-operated males without implants (shams), and compared male categories with respect to how they maintained body mass during the mating season. Somewhat unexpectedly, bibbed males consistently lost more body weight across all treatments and controls, although we could not verify that this translated into higher mortality in this short-lived animal (about 80% survive for one year only). However, bibbed males may invest more into "mating success" than nonbibbed males, which agrees with our experimental results and paternity data.